One for All, Each on Its Own: Analysing the Post-Soviet System of Collective Security - Erkomaishvili, David (Journal of Regional Security, 2018)
The fall of the Soviet Union in 1991 allowed independent states, which emerged in its place, to construct their own alignments. The choice of the case for empirical analysis had been made based on several unique characteristics. Orthodox Alliance Theory had almost never properly addressed alignments in the post-Soviet space due to the lack of access to information during the Soviet period – along with the structure of the state: only Soviet alignment policies were taken into consideration, instead of those of its constituent republics as well – and modest interest of alliance theorists in the region. Continued disintegration of the post-Soviet space, which has not stopped with the collapse of the Soviet Union but keeps fragmenting further, cre- ates a unique setting for researching the adequacy of Alliance Theory’s classic assumptions as well as developing new approaches. This work traces the development of the post-Soviet system of collective security and its subsequent transformation into a series of bilateral security rela- tions, along with the shortfall of multilateralism.